A Structural Semiotic Analysis on Fārūq Juwaidah’s Poem Fī ‘Ainaiki ‘Unwānī - Nahdliyyatul Azimah; Endah Kusumawati (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Institut Agama Islam Darullughah Wadda'wah Pasuruan, 2020)
Abstract The purpose of the research is to analyse the poem Fī ‘Ainaiki ‘Unwānī by Fārūq Juwaidah using structural-semiotic analysis study. The research method used is a qualitative-descriptive method with content analysis approach. The result of this research shows that the meaning in this poem is still spread and implied at the heuristic level. However, this poem indicates an idea of the feeling expressed from the two sides of woman and man lovers at the hermeneutic level. On one side, a woman feels concerned about his affection and doubts it. On another side, a man is promising an eternal love for her to answer her worries. Furthermore, structural analysis shows that this poem contains a lot of tasybīh that strengthens the lines with the theme of affection written by Fārūq Juwaidah in this poem. Keywords: Fārūq Juwaidah, Fī ‘Ainaiki ‘Unwānī, Structural-Semiotics.